2016
DOI: 10.1249/mss.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationship between Cardiorespiratory Fitness and Academic Achievement

Abstract: Consistently high and improvements in cardiorespiratory fitness are prospectively associated with better academic achievement especially in mother tongue and foreign language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
68
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 45 publications
10
68
2
4
Order By: Relevance
“…Our results were statistically significant with respect to mathematics grades and a longitudinal study in a Portuguese population found parallel results, as fit children that stayed fit and unfit children that became fit scored better in native language, but not in mathematics (Sardinha et al, 2016). Low scores in mathematics can explain these results, that are apparently contradictory to previous research.…”
Section: Discussionsupporting
confidence: 56%
“…Our results were statistically significant with respect to mathematics grades and a longitudinal study in a Portuguese population found parallel results, as fit children that stayed fit and unfit children that became fit scored better in native language, but not in mathematics (Sardinha et al, 2016). Low scores in mathematics can explain these results, that are apparently contradictory to previous research.…”
Section: Discussionsupporting
confidence: 56%
“…Health and sport programs are worthy crime prevention approaches. 28 There are also recognised relationships between physical activity and fitness level and academic achievement 29 as well as social and mental health benefits specific to Aboriginal and Torres Strait Islander populations. 30,31 However, a cautious approach to alluding to wider social benefits directly arising from individual programs should be taken in the absence of empirical evidence, as well as the direct effects of standalone programs on health.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of physical fitness are associated with academic performance and achievement in cross‐sectional and prospective studies . A few state‐level investigations with elementary school children have also examined the associations between fitness test performances and school and sociodemographic variables.…”
mentioning
confidence: 99%